Gonadal development in the freshwater crab Sylviocarcinus pictus (H. Milne Edwards, 1853) (Brachyura: Trichodactylidae) from the Guamá river, state of Pará, Brazil - Leiliane S. Silva; Jussara M. Martinelli-Lemos; Maria Auxiliadora P. Ferreira; Rossineide M. Rocha (Anais da Academia Brasileira de Ciências, 2012)
The development stages of male and female gonads in the freshwater crab Sylviocarcinus pictus (H. Milne Eduards, 1853) were described through macroscopic and microscopic (histology) examinations. The histological description was based on 40 specimens (20 each sex). Four gonadal development stages were found for females: immature, ripening, mature and spawned. The following female cells were found: ovogonia, oocytes in initial vitellogenesis, oocytes in advanced vitellogenesis, follicular cells and post-ovulatory follicles. Three development stages were found for males: immature, maturing and mature, with the indication of: spermatogonia, spermatocytes, spermatids, spermatozoids and spermatophores. These data suggest the pattern described in the literature. Size at sexual maturity was 32.3 mm of carapace width for males and 31.5 mm for females. The gonadal stages observed macroscopically by volume and color were validated through histological analysis and proved to be useful method for the rapid identification of sexual maturity in the species. The present study offers previously unpublished data on the reproductive biology of Sylviocarcinus pictus. Os estádios de desenvolvimento das gônadas de machos e fêmeas de caranguejos Sylviocarcinus pictus (H. Milne Eduards, 1853) foram descritos por meio de observações macroscópicas e microscópicas (técnica histológica). A descrição histológica foi baseada em 40 espécimes (20 de cada sexo). Foram identificados quatro estádios de desenvolvimento para as fêmeas: imaturo, em maturação, maturo e em reabsorção. As seguintes células foram encontradas: ovogônias, ovócitos em vitelogênese inicial, ovócitos em vitelogênese avançada, células foliculares e folículos pós-ovulatórios. Três estádios de desenvolvimento foram encontrados para os machos: imaturo, em maturação e maturo, com indicação de: espermatogônias, espermatócitos, espermátides, espermatozóides e espermatóforos. Tais dados sugerem o padrão descrito na literatura. O tamanho da maturidade sexual foi de 32,3 mm de largura da carapaça para machos e 31,5 mm para fêmeas. Os estádios gonadais observados macroscopicamente por meio do volume e da coloração das gônadas foram validados pela análise histológica, sendo um critério útil e ágil para a identificação da maturidade sexual para a espécie. O presente estudo oferece informações inéditas sobre a biologia reprodutiva de Sylviocarcinus pictus.